Double-rod metasurface for mid-infrared polarization conversion - 蒲洋;罗意;刘路;何德;徐洪艳;景洪伟;蒋亚东;刘志军 (Chinese physics B, 2018)
Resonant responses of metasurface enable effective control over the polarization properties of lights. In this paper,we demonstrate a double-rod metasurface for broadband polarization conversion in the mid-infrared region. The metasurface consists of a metallic double-rod array separated from a reflecting ground plane by a film of zinc selenide. By superimposing three localized resonances, cross polarization conversion is achieved over a bandwidth of 16.9 THz around the central frequency at 34.6 THz with conversion efficiency exceeding 70%. The polarization conversion performance is in qualitative agreement with simulation. The surface current distributions and electric field profiles of the resonant modes are discussed to analyze the underlying physical mechanism. Our demonstrated broadband polarization conversion has potential applications in the area of mid-infrared spectroscopy, communication, and sensing.